2013
DOI: 10.7314/apjcp.2013.14.1.405
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Bcl-3 Inhibits Cell Growth and Induces DNA Damage in HTLV-1-infected Cells)

Abstract: Oncoprotein Bcl-3 is perceived as an unusual member of IκB family since it can both stimulate and suppress NF-κB activation. Aberrant Bcl-3 results in increased cell proliferation and survival, suggesting a contribution to malignant potential and elevated levels of Bcl-3 have been observed in many HTLV-1-infected T cell lines and ATL cells. To investigate the specific roles of Bcl-3 in HTLV-1-infected cells, we knocked down Bcl-3 expression using shRNA and then examined the consequences with regard to DNA dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Early indications of a role for BCL3 in genome integrity were posited when BCL3 was shown to suppress p53 via upregulation of Hdm2 in response to UVB induced DNA damage of breast cancer cells [ 105 ] and when shRNA suppression of BCL3 was shown to induce aneuploidy in HeLa cells with accompanying increases in phospho-ATM, gamma-H2Ax and a concomitant decrease in phospho-CHK1 [ 114 ]. These observations were further supported by studies demonstrating a relative loss of DNA integrity when BCL3 was suppressed following human T cell leukemia virus Type 1 (HTLV1) challenge in T-cells [ 115 ] and a role in DNA break repair proposed after profound suppression of the double-strand DNA break repair protein DNA-PK in HeLa cells was observed when BCL3 was suppressed both before and after UVB irradiation [ 110 ].…”
Section: Bcl3 and Cancermentioning
confidence: 81%
“…Early indications of a role for BCL3 in genome integrity were posited when BCL3 was shown to suppress p53 via upregulation of Hdm2 in response to UVB induced DNA damage of breast cancer cells [ 105 ] and when shRNA suppression of BCL3 was shown to induce aneuploidy in HeLa cells with accompanying increases in phospho-ATM, gamma-H2Ax and a concomitant decrease in phospho-CHK1 [ 114 ]. These observations were further supported by studies demonstrating a relative loss of DNA integrity when BCL3 was suppressed following human T cell leukemia virus Type 1 (HTLV1) challenge in T-cells [ 115 ] and a role in DNA break repair proposed after profound suppression of the double-strand DNA break repair protein DNA-PK in HeLa cells was observed when BCL3 was suppressed both before and after UVB irradiation [ 110 ].…”
Section: Bcl3 and Cancermentioning
confidence: 81%
“…In studying the specific role of Bcl-3 in cells infected with human T cell leukemia virus type 1 (HTLV-1), Gao et al used shRNA to knock down the expression of Bcl-3. The experimental results revealed that Bcl-3 can promote DNA stability, cell growth and NF-kB activation in HTLV-1-infected cells (66). Moreover, Bcl-3 mutations in lymphocytes give rise to overexpression of IkB protein and uncontrolled cell proliferation, which lead to B-cell chronic lymphocytic leukemia (67).…”
Section: Bcl-3 Is Involved In Cell Survival and Apoptosismentioning
confidence: 99%
“…Cloning of chromosomal breakpoints found in chronic lymphocytic leukemia cells demonstrated that the t(14;19) chromosomal translocation results in the juxtaposition of the BCL3 gene with the immunoglobulin (Ig) heavy locus leading to the overexpression of Bcl-3 in leukemic cells [ 19 , 20 , 21 ]. Bcl-3 overexpression is also associated with a number of cancers that do not harbor BCL3 -associated translocations, including classical Hodgkin’s and peripheral T-cell lymphoma [ 22 ], chronic lymphocytic leukemia [ 23 ], adult T cell leukemia [ 24 ], and certain solid tumors [ 25 , 26 ].…”
Section: Bcl-3mentioning
confidence: 99%